Development of a Wayground-Based Educational Game Integrated with Discovery Learning for Social Studies Learning in Ninth Grade of Junior High School - Apriani, Dewi; Isa, Yamanto; Susila, Heni Rita (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This study aimed to develop an educational game-based learning media using the wayground platform integrated with the discovery learning approach for Grade ninth social studies learning. The study employed a Research and Development (R&D) design using the Dick and Carey instructional design model. The development process included needs Identify Instructional Goals. Conduct Instructional Analysis, Analyze Learners and Contexts, Write Performance Objectives, Develop Assessment Instruments, Develop Instructional Strategy, Develop and Select Instructional Materials, Design and Conduct Formative Evaluation, Revise Instruction, Design and Conduct Summative Evaluation. The research subjects consisted of Grade IX students of SMP Negeri 07 OKU, as well as media, instructional design, and subject matter experts. Data were collected through observations, interviews, and questionnaires and analyzed using descriptive qualitative and quantitative techniques. The results showed that the developed media achieved a feasibility score of 85.42% from media experts, 85.00% from instructional design experts, and 89.71% from subject matter experts, indicating that the product was categorized as feasible to very feasible. Product testing also revealed positive student responses, particularly in terms of engagement, motivation, participation, and ease of understanding learning materials. The integration of gamification elements and Discovery Learning syntax created a more interactive and student-centered learning environment. Therefore, the developed educational game-based media has significant potential to support effective and meaningful social studies learning in the digital era.